STRATEGI EFISIENSI WAKTU DALAM PROSES PEMBUATAN FILM DI BALIK RAUT SUNYI - Dewi, Septi Sari; Citra Dewi Utami (TEXTURE Art and Culture Journal, 2024)
Film Di Balik Raut Sunyi addresses mental health issues arising from the writer's concern over the lack of awareness and support for these issues, particularly social anxiety disorder. In the film Di Balik Rraut Sunyi this issue is portrayed through the story of a clown named Brian who appears to be fine when he is in character but suffers from social anxiety when he is himself. The production of the film Di Balik Raut Sunyi was managed using a time efficiency strategy, with the writer taking on the role of producer. The producer plays a crucial role in the filmmaking process, which involves script development, pre-production, production, and post- production. The time efficiency strategy was implemented during the pre-production phase by combining the Pre-Production Meeting (PPM) with other stages such as reading, recce, wardrobe and makeup fitting. Additionally, this strategy was used to plan the shooting days and schedule based on the scene breakdown in the script. The combination of these processes demonstrates that a time efficiency strategy can be applied to maximize the filmmaking process within a limited timeframe.